Studying the Effect of some Biotic and Abiotic factors on organic and Inorganic Mercury Concentrations in the new Coastal Sediments of Latakia City - حسام الدين لايقه; بدر العلي; علا شكوحي (Latakia University Journal -Biological Sciences Series, 2022)
The aim of this research was to determine the concentrations of (organic -total) mercury in new marine sediment by using atomic absorption spectrophotometer (Flame-AAS technology) in different sites of Lattakia city coastal during the summer of 2020 and winter of 2021 and its relationship to some hydrochemical factors (temperature, salinity and pH) and the density of bacteria. The results showed that highest values ​​of mercury concentrations (both organic and inorganic) were recorded in the sites affected by different human activities (St1: Apamea, St3: Sakiyat Moussa, St4: Sports City, St5: estuary of the North Kabir River) en comparison to the High Institute of Marine Research site which is relatively far from the sources of pollution: St2. The results showed that the change in mercury concentrations was related to the abundance of bacteria on the one hand, and to hydrochemical factors on the other. Total elemental mercury concentrations ranged between (1719-563 µg/kg) in summer and (1269-365 µg/kg) in winter, and organic mercury concentrations ranged between (1350-438 µg/kg) in summer and (294-10 µg/kg) in winter. The results showed a clear influence of biological factors (general count of bacteria) on total mercury concentrations in general, and organic mercury in particular.